Winter Adaptations in the Willow Ptarmigan - Andreev, A.V. (ARCTIC, 1991)
The willow ptarmigan, Lagopus lagopus, dwells in a vast area with a variety of climatic and biotic conditions. Populations from northeast Asia must cope with extremely low temperatures along with progressive depletion of food resources throughout the winter. Being unable to roost in the snow at -40 degrees C, a ptarmigan's daily life would cost 3.2-3.5 basal metabolic rate (BM), but by burrowing in snow for up to 21 hours per day, the bird saves at least 1.0 BM. To meet daily energy demands on a midwinter day a ptarmigan needs about 60 g of food (dry weight), consisting mostly of willow buds and twigs. Early in winter the diet contains 12-15% protein and 20-25% fiber, declining later to 7-8% protein and increasing up to 35% fiber. Nitrogen concentration, crucial for food digestibility, declines by half (from 0.35 to 0.18%) during the six winter months. Nitrogen also causes increased food consumption in a feedback pattern. Nevertheless, many birds lose body weight constantly. To recover losses they need a more nutritious diet after the snow starts to melt. Thus, the willow ptarmigan's adaptation to the polar winter appears as an individual balancing act within a few specific limits. Higher density of conspecific birds, colder winters and/or later springs may cause physiological damage to individuals, which eventually would lower the reproduction rate within the breeding population.Key words: willow ptarmigan, winter ecology, metabolic rates, food quality, fiber digestion Mots clés: lagopède des saules, écologie hivernale, taux de métabolisme, qualité alimentaire, digestion des fibres